2015
DOI: 10.1039/c5ra14704b
|View full text |Cite
|
Sign up to set email alerts
|

β-NiMoO4nanowire arrays grown on carbon cloth for 3D solid asymmetry supercapacitors

Abstract: A β-NiMoO4 NW supercapacitor lights one LED for 260 s and delivers a large specific capacitance (414.7 F g−1 at 0.25 A g−1), high energy density (36.86 W h kg−1), a maximum power density of 1100 W kg−1 and 65.96% capacity retention after 6000 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…NiCoMn 2 oxide exhibits high specic capacitance, good rate capability and excellent cyclic stability, showing great superiority compared to state-of-the-art metal oxide-based materials. [29][30][31] The outstanding electrochemical performance of NiCoMn 2 oxide should be associated with the synergistic effect between Ni, Co and Mn elements, as well as the advantageous structure and the appropriate composition. The appropriate addition of Mn can impel the formation of three-dimensional network structure consisting of nanoneedles and nanosheets, which is particularly benecial for fast transfer of electrolyte ions to electrode surface, resulting in improved electrochemical performance.…”
Section: Resultsmentioning
confidence: 99%
“…NiCoMn 2 oxide exhibits high specic capacitance, good rate capability and excellent cyclic stability, showing great superiority compared to state-of-the-art metal oxide-based materials. [29][30][31] The outstanding electrochemical performance of NiCoMn 2 oxide should be associated with the synergistic effect between Ni, Co and Mn elements, as well as the advantageous structure and the appropriate composition. The appropriate addition of Mn can impel the formation of three-dimensional network structure consisting of nanoneedles and nanosheets, which is particularly benecial for fast transfer of electrolyte ions to electrode surface, resulting in improved electrochemical performance.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the ESM template, or a combination of the template and the urea additive, in some way favours formation of the -NiMoO 4 crystal structure under these relatively mild conditions. Synthesis of β-NiMoO 4 under similarly mild conditions has been reported with a carbon cloth template [38]. Recently, researchers compared hydrothermal (using an autoclave) and sol-gel methods for the synthesis of NiMoO 4 and showed that formation of -NiMoO 4 is more likely using the former but the sol gel method resulted in the formation of β-NiMoO 4 .…”
Section: Materials Characterisationmentioning
confidence: 84%
“…The faradaic redox behaviour of the ESM-NiMoO 4 material is significantly less than that measured in the nontemplated material (Figure 4a, b) with the CV curves exhibiting a more quasi-rectangular profile. This profile indicates that the ESM templated material is behaving as a supercapacitor with a combination of a reversible electron transfer process from the Ni +2 /Ni +3 redox couple and a surface area related electric double layer charge storage mechanism [27,30,38,44]. The triangular shape of the galvanostatic charge-discharge profile (Figure 4c) is typical of hybrid supercapacitor behaviour and suggests superior conductivity and capacitance [38].…”
Section: Electrochemical Performancementioning
confidence: 94%
See 1 more Smart Citation
“…无 机 材 料 学 报 第 32 卷 量储存已经成为制约现代社会发展的一个重要问题。在 诸多电化学储能器件中, 超级电容器(Supercapacitors, SCs)因其高功率密度、长循环寿命、脉冲充放电等 特性而引起科学界和工业界的广泛关注 [1][2][3][4] 。为了满 足日益严峻的实际需求, 炭材料 [5][6][7] 、 导电聚合物 [8] 、 金属化合物(金属氢氧化物 [9] 、金属氧化物 [10] 、金属 硫化物 [11] 、金属氮化物 [12] 和金属磷化物 [13] )及其复 合材料 [14][15][16] 等被应用于高性能 SCs 电极。这些活性 材料按照储能机制通常可以分为两类: 双电层储能 类活性材料和法拉第赝电容储能类活性材料。一般 而言, 由双电层类活性材料构成的 SC 具有良好的 倍率特性和优异的循环性能, 但是能量密度相对较 低; 而赝电容材料因其可以提供可观的能量输出, 比双电层类材料具有更高的容量。 为了制备高能量密度 SCs, 研究工作者将目光 聚焦在赝电容材料上。人们发现二氧化钌(RuO 2 )具 有高的电化学活性, 是一种理想的 SC 用活性材料, 但是 Ru 的价格高昂、 储量低限制了其规模化应用 [17] 。 研 究 发 现 储 量 丰 富 的 过 渡 金 属 氧 化 物 (Transition Metal Oxides, TMOs), 如 NiO [18] 、Co 3 O 4 [19] 、V 2 O 5 [20][21] 、 MoO 3 [22] 、MnO 2 [23] 和 Fe 2 O 3 [24] [25] 。除了反应温度之外, 体系中的液相体积、溶 解盐的种类数量等都对产物形貌产生明显影响 [26][27] 。 通过这种方法还可以低温制备特殊氧化态的过渡金 属化合物, 是一种高效低成本的合成技术。该方法 过程相对简单, 反应条件相对温和, 易于控制, 可 以有效防止有毒有害物质的挥发, 产物纯度高, 晶 粒尺寸大, 可以实现单分散颗粒的可控制备。表 1 列举了一些溶剂热/水热合成 BTMOs 的相关条件, 从表中可以看出这种方法可以实现从一维到三维材 料 BTMOs 的可控制备 [27][28][29][30] [32] Fig. 2 FE-SEM and TEM images of porous NiCo 2 O 4 microsphere [32] 以免去粘结剂的使用, 这不仅可以减小接触电阻, 还可以提高能量密度 [33][34][35] 。且多孔基底的使用还可 以增加活性位点的数量, 使沉积的 BTMOs 可以有更 多的机会与电解液接触, 从而提高 BTMOs 的有效利 用率, 保证材料高容量的发挥。电沉积法简单快捷, 产物形貌尺寸均匀, 但产量低阻碍了其实际应用。…”
unclassified